Pengaruh Partisipasi Anggaran terhadap Kinerja Manajerial dengan Organizational Citizenship Behavior dan Komitmen Organisasi sebagai Pemoderasi - Dewi, Cok Istri Intan Paramita; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 21 No 2 (2017)DO - 10.24843/EJA.2017.v21.i02.p24, 2017)
ABSTRACT Managerial performance is the level of managerial skills in implementing management activities so that budget objectives are achieved and subordinates get the opportunity to participate in the budgeting process. The participation of budget preparation is expected to improve managerial performance. The existence of inconsistent results, and possibly caused by contingencies such as organizational citizenship behavior and organizational commitment. This study aims to provide empirical evidence on the influence of budgetary participation on managerial performance with organizational citizenship behavior and organizational commitment as a moderating variable. This research was conducted in seven branch offices of PT. Bali Regional Development Bank uses the type of qualitative and quantitative data sourced from the primary and secondary data collected through interviews and questionnaires. Questionnaires were distributed to 66 officials involved in the budgeting process. Questionnaires that can be processed as many as 57 questionnaires. Data have been tested and qualified instrument test (validity and reliability test) and classical assumption test (normality test and heteroskedatisitas). Analysis technique used in this research is multiple linear regression analysis with Moderated Regression Analysis (MRA). The results showed that budgetary participation had no effect on managerial performance, organizational citizenship behavior could strengthen the positive influence of budget participation relation on managerial performance, and organizational commitment was unable to reinforce the positive influence of budgetary participation on managerial performance. Keywords : Budgetary Participation, Organizational Citizenship Behavior, Organizational Commitment, Managerial Performance